The QBO Modulation on CO Distribution in the UTLS Over the Asian Monsoon Region During Boreal Summer - He, Xin; Luo, Jiali; Xu, Xiran; Ren, Lu; Tian, Hongying; Shang, Lin; Xu, Pingping (Frontiers in Earth Science, 2021)
Using the Microwave Limb Sounding (MLS) measurements and the National Center for Environmental Prediction/National Center for Atmospheric Research (NCEP/NCAR) reanalysis product, we have investigated the response of carbon monoxide (CO) mixing ratio within the Asian Summer Monsoon Anticyclone (ASMA) region to the Quasi-Biennial Oscillation (QBO) and the potential dynamical mechanisms behind. The results show that the mixing ratio of CO within the ASMA is significantly higher at both 100 hPa and 147 hPa in the east phase of QBO (EQBO) years than in the west phase of QBO (WQBO) years, especially in the eastern part of the ASMA. The CO difference between EQBO and WQBO years is consistent with interannual variation of the location and strength of the ASMA. Specifically, during the EQBO years, the area of the ASMA reduces to the southeast in the upper troposphere, while the westerly jet on the north side of the anticyclone and the southerly winds on the west side of the anticyclone both strengthen. These variations are associated with tropospheric circulation anomalies. The ascending motions over the Tibetan Plateau (TP) enhance during the EQBO years, which is correlated with the relatively high CO at 100 hPa. Consistently, an anomalous cyclonic circulation is found at 500 hPa over the TP when the QBO is on its east phase, which promotes convergence of the air mass and carries CO from surface to the Upper Troposphere and Lower Stratosphere (UTLS).